1985
DOI: 10.1073/pnas.82.11.3884
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-associated chromosomal changes in human mesothelial cells.

Abstract: Replicative cultures of human pleural mesothelial cells were established from noncancerous adult donors. The cells exhibited normal mesothelial cell characteristics including keratin, hyaluronic acid mucin, and long branched microvilli, and they retained the normal human karyotype until senescence. The mesothelial cells were 10 and 100 times more sensitive to the cytotoxic effects of asbestos fibers than normal human bronchial epithelial or fibroblastic cells, respectively. In addition, cultures of mesothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(64 citation statements)
references
References 25 publications
3
61
0
Order By: Relevance
“…Models of transcript profiling for discrimination of toxic and nontoxic compounds in liver and other organs have also been developed in rodents (18), confirming the hypothesis that predictive modeling for classification of toxic agents and carcinogens is feasible. Here we used toxicogenomic approaches in human mesothelial cells, a cell type exquisitely sensitive to asbestos (19) and human contact-inhibited ovarian epithelial cells, a cell type not linked to carcinogenesis by asbestos, to determine whether the magnitude of altered gene expression by insoluble particulates correlated with their toxicity to cells and documented pathogenicity in humans. Although a recent study has examined gene expression profiles comparatively in crocidolite asbestos-exposed human lung adenocarcinoma (A549) and SV40-immortalized bronchial (BEAS-2B) or pleural mesothelial cell lines (MET5A) by cluster analysis (20), our studies are the first to examine gene expression changes by asbestos in comparison to other well-characterized particles in a human cell line that exhibits features of normal mesothelial cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…Models of transcript profiling for discrimination of toxic and nontoxic compounds in liver and other organs have also been developed in rodents (18), confirming the hypothesis that predictive modeling for classification of toxic agents and carcinogens is feasible. Here we used toxicogenomic approaches in human mesothelial cells, a cell type exquisitely sensitive to asbestos (19) and human contact-inhibited ovarian epithelial cells, a cell type not linked to carcinogenesis by asbestos, to determine whether the magnitude of altered gene expression by insoluble particulates correlated with their toxicity to cells and documented pathogenicity in humans. Although a recent study has examined gene expression profiles comparatively in crocidolite asbestos-exposed human lung adenocarcinoma (A549) and SV40-immortalized bronchial (BEAS-2B) or pleural mesothelial cell lines (MET5A) by cluster analysis (20), our studies are the first to examine gene expression changes by asbestos in comparison to other well-characterized particles in a human cell line that exhibits features of normal mesothelial cells (5).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of mitotic disturbances in SHE cells, Dopp et al (81) observed kinetochore staining in the micronucleus formed after asbestos treatment, indicating that whole chromosomes have been lost. Numerical chromosome abnormalities have been observed in human (91) and rat mesothelial cells (84) Table 9. The feeding of mice with asbestos did not result in chromosome abnormalities in germinal cells (106).…”
Section: Chromosome Damagementioning
confidence: 99%
“…Conventional dielectrophoresis and ROT measurements have revealed that significant differences exist in the dielectric properties of cells in different physiologic states (14, (40), induction of damage to chromosomes (41) and DNA (40), transformation (42), and apoptosis (43). To date, almost nothing is known about early surface property changes of the cellular membrane and interior dielectric changes of asbestostreated cells.…”
Section: Discussionmentioning
confidence: 99%